Analysis of fundamental dependencies between manufacturing and processing Tailored Blanks in sheet-bulk metal forming processes - Schulte, Robert Karl; Hildenbrand, Philipp; Vogel, Manfred; Lechner, Michael; Merklein, Marion (International Conference on the Technology of Plasticity, ICTP 2017, 17-22 September 2017, Cambridge, United Kingdom, 2017)
LFT Import::2019-08-05 (2232)
Keywords: Cold forming; Deep drawing; Tailored Blank

A new strategy for manufacturing tailored blanks by a flexible rolling process - Hildenbrand, Philipp; Lechner, Michael; Merklein, Marion (Materials Science Forum, 2016)
LFT Import::2019-07-29 (2143)
Keywords: Forming; Rolling; Sheet metal

Application of Process adapted semi-finished Parts for the Production of Thin-walled Components via Sheet-Bulk Forming - Merklein, Marion; Hildenbrand, Philipp; Schneider, Thomas (AutoMetForm / SFU 2014, 2014)
LFT Import::2019-08-05 (2038)

Data-Based Control of A Multi-Step Forming Process - Schulte, Robert Karl; Frey, Philipp; Hildenbrand, Philipp; Vogel, Manfred; Betz, C.; Lechner, Michael; Merklein, Marion (Proc. International Deep Drawing Research Group Conf. IDDRG 2017, 2017)
LFT Import::2019-08-05 (2253)

Data-driven Model Development for Quality Prediction in Forming Technology - Kirchen, Iris; Vogel-Heuser, Birgit; Hildenbrand, Philipp; Schulte, Robert Karl; Vogel, Manfred; Lechner, Michael; Merklein, Marion (15th IEEE International Conference on Industrial Informatics (INDIN), 2017)
this investigation data recorded from a flexible rolling process is processed by data driven methods to develop a quality prediction model for manufactured blanks. A concept for an incremental prediction method is proposed, which takes into account the specific character of the discrete manufacturing process. The method is evaluated based on a data set of process and quality data provided by a test rig. By the example of a specific quality parameter the effectiveness of the proposed method is confirmed. A precise quality prediction model is developed, which predicts the quality value with a high accuracy.
LFT Import::2019-08-05 (2252)
Keywords: automated Production Systems; data analytics; quality prediction

Designing, manufacturing and processing of Tailored Blanks in a sheet-bulk metal forming process - Schulte, Robert Karl; Hildenbrand, Philipp; Lechner, Michael; Merklein, Marion (45th SME North American Manufacturing Research Conference, NAMRC 45, LA, USA, 2017)
Sheet-bulk metal forming is an innovative method for the manufacturing of functional components by applying bulk metal forming processes or combined sheet and bulk metal forming processes to sheet metal. The investigated process combines deep drawing and upsetting. Occurring 2D and 3D stress and strain states lead to challenges regarding the material flow control during the forming process to ensure a high die filling and accurate part geometry. Regarding these challenges, the application of conventional semi-finished products is not expedient wherefore Tailored Blanks with a process adapted sheet thickness distribution are applied to the forming process. The Tailored Blank geometry is designed by a numerical analysis and manufactured by an orbital forming process considering the resulting geometric part properties during deep drawing and upsetting. Therefore, the whole process chain from the conventional circular blank to the finished functional component is linked and modelled. This enables a realistic description of the part properties as the effective plastic strain caused in the manufacturing of semi-finished products is taken into account in the processing of the material. Subsequently the results are verified by experimental tests.
LFT Import::2019-08-05 (2231)
Keywords: Deep drawing; Finite element method (FEM); Forming; Sheet metal

Development of a feature adapted measurement evaluation strategy - Loderer, Andreas; Hausotte, Tino; Steinmann, Paul; Merklein, Marion; Landkammer, Philipp; Hildenbrand, Philipp; Schneider, Thomas (MacroScale 2014 - Recent developments in traceable dimensional measurements, 2015)
This article describes a methodical approach for developing a feature adapted measurement evaluation strategy using the example of a multi-scale multi-sensor fringe projection system. In a first step calibrated standard features were selected and measured in the next step by different fringe projection sensors with varying measuring range and resolution. For selecting which sensor is most appropriate for which feature the standard deviation as well as the deviation between calibrated values and measured values were considered. Finally the results were summarized in a decision matrix, which helps to select a feature adapted measurement strategy.

Ductile Damage and Fatigue Behavior of Semi-Finished Tailored Blanks for Sheet-Bulk Metal Forming Processes - Besserer, Hans-Bernward; Hildenbrand, Philipp; Gerstein, Gregory; Rodman, Dmytro; Nuernberger, Florian; Merklein, Marion; Maier, Hans Juergen (Journal of Materials Engineering and Performance, 2016)
To produce parts from sheet metal with thickened functional elements, bulk forming operations can be employed. For this new process class, the term sheet-bulk metal forming has been established recently. Since sheet-bulk metal forming processes such as orbital forming generates triaxial stress and strain states, ductile damage is induced in the form of voids in the microstructure. Typical parts will experience cyclic loads during service, and thus, the influence of ductile damage on the fatigue life of parts manufactured by orbital forming is of interest. Both the formation and growth of voids were characterized following this forming process and then compared to the as-received condition of the ferritic deep drawing steel DC04 chosen for this study. Subsequent to the forming operation, the specimens were fatigued and the evolution of ductile damage and the rearrangement of the dislocation networks occurring during cyclic loading were determined. It was shown, that despite an increased ductile damage due to the forming process, the induced strain hardening has a positive effect on the fatigue life of the material. However, by analyzing the fatigued specimens a development of the ductile damage by an increasing number of voids and a change in the void shape were detected.
LFT Import::2019-07-29 (2149)
Keywords: DC04; ductile damage; orbital forming; sheet-bulk metal forming

Entwicklung einer Methodik zur Herstellung von Tailored Blanks mit definierten Halbzeugeigenschaften durch einen Taumelprozess - Hildenbrand, Philipp (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2019)
Sustainable production by a defined usage and thus saving of materials along the product development process is one central aspect to reduce emissions and contribute to climate protection. Improving the material efficiency can be realized by the application of process adapted semi-finished parts, so called tailored blanks which can for example be manufac-tured an orbital forming process. In this context, the central objective of this work is the fundamental scientific investigation of an orbital forming process for manufacturing tailored blanks with defined part properties out of steel materials with different strength. To achieve the set objective, the fundamental causeeffect relationships as well as the influence on the resulting part properties will be identified on the basis of the main process parameters. Based on these results, process limits will be identified and a methodology will be derived which enables a defined adjustment of the part properties. This methodology will be validated by additional experiments in order to verify made statements regarding the generalization of the findings. Overall, this leads to a broad and deeper process understanding regarding the influence of different process parameters on the properties of orbital formed tailored blanks out of various steels. This enables the realization of defined properties specifically adapted for their field of application and in the end an improved material efficiency and saving of resource

Flexible Rolling of Process Adapted Semi-finished Parts and its Application in a Sheet-Bulk Metal Forming Process - Hildenbrand, Philipp; Schneider, Thomas; Merklein, Marion (Key Engineering Materials, 2015)
By applying bulk forming processes on sheet metals, thin-walled functional components with locally restricted wall thickness variations can be manufactured by forming operations. Using tailored blanks with a modified sheet thickness gradient instead of conventional blanks, an efficient controlling of the material flow can be achieved. One possible process to manufacture these semifinished parts is a flexible rolling process. Based on an established process strategy new results for steels of differing strength and work-hardening behavior are presented in this paper. The influences of each material on the resulting process forces and blank properties regarding the same target geometry are discussed. The tailored blanks are hereby analyzed by their geometrical dimensions, like sheet thickness, and their mechanical properties, e.g. hardness distribution. Additionally, the possibilities of processing these tailored blanks in a deep-drawing and upsetting process are presented with a hereby focus on the residual formability of the tailored blanks.
LFT Import::2019-07-29 (2069)
Keywords: Forming; Rolling; Sheet metal

Induction heat treatment of sheet-bulk metal-formed parts assisted by water-air spray cooling - Besserer, Hans-Bernward; Dalinger, Andrej; Rodman, Dmytro; Nuernberger, Florian; Hildenbrand, Philipp; Merklein, Marion; Maier, Hans Juergen (Steel Research International, 2016)
In order to produce components with massive secondary functional elements from sheet metal bulk forming operations, termed sheet-bulk metal forming, can be applied. Owing to high, three-dimensional stress and strain states present during sheet-bulk metal forming, ductile damage occurs in the form of micro-voids. Depending on the material flow properties, tensile residual stresses can also be present in the components' formed functional elements. During service, the components are subjected to cyclic loading via these functional elements, and tensile residual stresses exert an unfavorable influence on crack initiation and crack growth, and therefore on the fatigue life. Following the forming process, temperature and microstructurally related compressive residual stresses can be induced by local heat treating of the surface. These residual stresses can counteract potential crack initiation on the surface or in the subsurface regions. In the present study, the adjustability of the residual stress state is investigated using a workpiece manufactured by orbital cold-forming, which possesses an accumulation of material in its edge region. Based on residual stress measurements in the workpiece's edge region using x-ray diffractometry, it is possible to verify the compressive residual stresses adjusted by varying the cooling conditions.
LFT Import::2019-07-29 (2150)
Keywords: DP600; induction heat treatment; orbital forming; residual stress; water–air spray cooling

Influence of tailored blanks on forming of cold forged functional elements in a sheet bulk metal forming process - Gröbel, Daniel; Hildenbrand, Philipp; Engel, Ulf; Merklein, Marion (Proceedings METEC & 2nd ESTAT, 2015)
LFT Import::2019-08-05 (2080)

Inkrementelles Umformen dünnwandiger Funktionsbauteile unter Einsatz prozessangepasster Halbzeuge durch Verfahren der Blechmassivumformung - Hildenbrand, Philipp; Sieczkarek, P.; Matthias, S.; Löffler, Maria; Besserer, H. (Tagungsband zum 18. Workshop Simulation in der Umformtechnik & 3. Industriekolloquium Blechmassivumformung 2015 - DFG Transregio 73, 2015)
LFT Import::2019-08-05 (2078)

Innovative approaches for controlling the material flow in sheet-bulk metal forming processes - Merklein, Marion; Lechner, Michael; Gröbel, Daniel; Löffler, Maria; Schneider, Thomas; Schulte, Robert Karl; Hildenbrand, Philipp (Manufacturing Review, 2016)
Using sheet-bulk metal forming processes the application of bulk forming operations on sheet metals enables the manufacturing of functional components with local wall thickness variations. As these processes come along with a two- and three-dimensional material flow, the control of the material flow is crucial for ensuring a proper filling of functional elements and thus ensuring the components quality. Controlling the material flow can be achieved by different solutions: the local adaption of tribological conditions and the application of process adapted semi-finished parts. In this paper, both solutions as well as their general qualification in two sheet-bulk metal forming processes are presented.
LFT Import::2019-07-29 (2144)
Keywords: Forming; Material flow; Processes

Manufacturing of functional elements by sheet-bulk metal forming processes - Gröbel, Daniel; Schulte, Robert Karl; Hildenbrand, Philipp; Lechner, Michael; Engel, Ulf; Sieczkarek, P.; Wernicke, Sebastian; Gies, Soeren; Tekkaya, A. E.; Behrens, B. A.; Huebner, S.; Vucetic, M.; et al. (Production Engineering, 2016)
Due to increasing economic and ecological restrictions, conventional sheet and bulk forming operations often reach their limits with regard to part weight and functional integration. One solution to meet those challenges is provided by sheet-bulk metal forming (SBMF) processes. SBMF is defined as the application of bulk forming operations on sheet metal. SBMF can be combined with conventional sheet forming operations and offers the opportunity to form highly functional integrated parts out of sheet metal. It contains the benefit of an optimization of the part weight and a shortening of the process chain. Recent research has found different solutions regarding the actual implementation of SBMF in several process variants. In this paper, a categorisation for functional elements on sheet metal parts is proposed. A selection of possible approaches for their manufacturing is presented. The process variants are compared by means of the main process characteristics. By these means, the choice of a suitable option shall be facilitated for practical manufacturing design and for a particular relevant product.
LFT Import::2019-07-29 (2152)
Keywords: Flow control; Sheet-bulk metal forming; Tailored blanks; Tailored surfaces

Manufacturing of tailored blanks by flexible rolling and its application in a sheet-bulk metal forming process - Vogel, Manfred; Lechner, Michael; Hildenbrand, Philipp; Schulte, Robert Karl; Merklein, Marion (Proceedings SCT2017, 2017)
LFT Import::2019-08-05 (2229)

New process strategies to manufacture tailored blanks out of DP600 by orbital forming - Hildenbrand, Philipp; Schulte, Robert Karl; Merklein, Marion (Applied Mechanics and Materials, 2015)
LFT Import::2019-07-29 (2115)

Orbital forming of tailored blanks with two-sided local material thickening - Hildenbrand, Philipp; Lechner, Michael; Vogel, Manfred; Herrmann, H.; Merklein, Marion (International Journal of Advanced Manufacturing Technology, 2018)
Economic and ecological demands like saving resources and improved material efficiency can be achieved by the application of process adapted semi-finished parts, so-called tailored blanks, for the manufacturing of for example gearings or synchronizer rings. Functional components require the locally restricted distribution of an adequate amount of material at defined positions in order to properly form functional elements like gearings or carriers. As these elements can be formed on one or both sides of the component, an appropriate material provision on one or both sides of the sheet metal is necessary. Having material thickenings on two sides lead to the interaction between both sides for example with regard to the maximum die filling. One process to produce tailored blanks is orbital forming. While manufacturing these tailored blanks with a local material thickening on one side of the sheet metal is state-of-the-art, the realization of these tailored blanks on both sides has not been investigated yet. In this paper, the results regarding the manufacturing of tailored blanks with a two-sided local material thickening will be presented for the first time. By analyzing three different tailored blank geometries, the influence of the interactions of two-sided material thickenings will be investigated. The results will be evaluated in terms of the resulting geometrical and mechanical properties.
LFT Import::2019-07-29 (2310)
Keywords: Forming; Orbital forming; Sheet-bulk metal forming; Tailored blank

Potenziale und Grenzen der Simulation in der Fertigungstechnik - Merklein, Marion; Andreas, Kolja; Gröbel, Daniel; Hildenbrand, Philipp; Müller, Martin; Noneder, Johannes; Zimmermann, Andrea; Schneider, Thomas; Vierzigmann, Ulrich (Tagungsband 15. RoundTable - Simulating Manufacturing, 2014)
LFT Import::2019-08-05 (2021)

Sheet-bulk metal forming – forming of functional components from sheet metals - Merklein, Marion; Gröbel, Daniel; Löffler, Maria; Schneider, Thomas; Hildenbrand, Philipp (Proceedings of the 4th International Conference on New Forming Technology, 2015)
LFT Import::2019-08-05 (2116)

Umformtechnische Herstellung von Funktionsbauteilen aus Tailored Blanks durch Blechmassivumformverfahren - Schulte, Robert Karl; Lechner, Michael; Vogel, Manfred; Hildenbrand, Philipp; Merklein, Marion (22. Umformtechnisches Kolloquium Hannover – Innovationspotentiale in der Umformtechnik. 15./16.03.2017, 2017)
LFT Import::2019-08-05 (2230)